Analisis Penilaian Hasil Belajar Dalam Ranah Kognitif, Afektif, dan Psikomotorik Dalam Proses Pembelajaran - Nabila Bilqisti; Khairu Riski; Mutia (Malewa: Journal of Multidisciplinary Educational Research, 2026)
Assessment of learning outcomes is an important part of the educational process because it is used to determine the level of student competency achievement after participating in learning activities. Assessment does not only focus on the final learning outcomes, but also includes the learning process experienced by students during the learning activities. In education, assessment of learning outcomes covers three main domains: cognitive, affective, and psychomotor. This study aims to explain the concept of learning process assessment and assessment of learning outcomes in the cognitive, affective, and psychomotor domains. The research method used is library research by reviewing various relevant books and journals. The results of the discussion indicate that assessment of the learning process functions to monitor student development during the learning process. Assessment of the cognitive domain is used to measure students' thinking abilities, the affective domain to assess students' attitudes and values, while the psychomotor domain is used to assess students' skills and practical abilities. With proper assessment implementation, teachers can obtain a comprehensive picture of student learning development.